Uncommon presentation of complicated internal hernia through the appendices epiploicae ring of adhesion: a clinical case study - Ghali, Mohamed Said; Shehata, Mona S.; Al Obahi, Mohammed; Al-Zoubi, Raed M.; Zarour, Ahmad (Frontiers in Surgery, 2024)
Background: Internal hernias are infrequent, yet serious, medical conditions with potentially severe consequences. An internal hernia resulting from an Appendices epiploicae (AE) ring is an especially rare cause, with a mere nine documented instances worldwide.Case Report: This report presents the case of a 58-year-old male who suffered from an internal hernia originating from an AE ring. The condition led to a gangrenous small bowel, which was treated by laparotomy and resection of the affected segment, followed by primary anastomosis. The postoperative recovery was favorable.Internal hernias, although rare, warrant immediate attention and early intervention to preclude detrimental outcomes, as illustrated in this particular case.